Modeling of vertical transmission and pathogenesis of cytomegalovirus in pregnancy: Opportunities and challenges - Kirschen, Gregory W.; Burd, Irina (Frontiers in Virology, 2023)
In addition to facilitating nutrient, oxygen, and waste transfer between developing fetus and mother, the placenta provides important immune barrier function against infection. Elucidation of the complexity of placental barrier function at the maternal-fetal interface has been greatly aided through experimental model organism systems. In this review, we focus on models of vertical transmission of cytomegalovirus (CMV), a ubiquitous double-stranded DNA viruses whose vertical transmission during pregnancy can lead to devastating neurological and obstetric sequelae. We review the current evidence related to guinea pig and murine models of congenital CMV infection, discuss the possible translatability of a non-human primate model, and conclude with recently developed technology using human placental organoids.